PERHITUNGAN NILAI CHART DATUM STASIUN PASANG SURUT JEPARA BERDASARKAN PERIODE PERGERAKAN BULAN, BUMI, DAN MATAHARI MENGGUNAKAN DATA PASUT TAHUN 1994 S.D 2013 - , ISNA USWATUN KH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The datum to which depths on a chart are referred is known as the chart datum. The determination of a chart datum is connected with the tides on a location. Tides on The Earth it is always changing in accordance with the position of the moon and the sun in its orbit which has a specific period. The aim of this research was to analysis the effect of moon, earth, and sun motions periods to define the chart datum values using 4 periods, which are 1 month, 1 year, 8.85 year, and 18.6 year. The research was conducted using tidal data of obtained from BIG, started from 1994 until 2013 in Jepara Tidal Station. The Method of the research consist of several steps. First, preliminary quality control of tidal data was done global test. Second, tidal harmonic analysis done by least-square methods which is assisted by T_tide v 1.3. Third, calculation of chart datum value based on DISHIDROS and IHO equationâs. The results from this research showed that the quality of 18.6 year tidal data was not good, since contain gap data almost 22.2 %. Therefore, the longest tidal data with good quality that is 14 year was used as a reference period instead of 18.6 year period. The Analysis of longest periode tidal data can separate out more constituens in the tidal potential from observations. Based on that result, the value of chart datum that generated between 14 year and 8.85 year tidal data almost same and the difference of the varian value is smaller than the shorter period. Finally, the optimum and efficient period data is 8.85 year period. The chart datum value for Jepara Tidal Station is 31.7724 cm based on DISHIDROS equationâs and 0.5418 cm based on IHO equationâs.